The slippery slope to genocide reducing identity conflicts and preventing mass murder - Zartman, I. William; Anstey, Mark.; Meerts, Paul. (New York : Oxford University Press, 2012)
In this volume, noted thinkers and practitioners of conflict management present ideas on how to prevent identity issues from causing fear and escalating into genocide. They focus on measures for handling the internal dynamics of parties facing identity conflicts, as well as considerations for arranging external assistance.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 20, 2012).
Includes bibliographical references and index.
Keywords: Genocide -- Prevention; Ethnic conflict; Ethnic groups